"Socio-Economic Status Of Particularly Vulnerable Tribal Groups (Pvtgs) In Karnataka: A Comprehensive Study" (Journal of Namibian Studies : History Politics Culture, 2023)
The present study aims to assess the socio-economic status of PVTGs in Karnataka, which includes Jenukuruba tribe from Hunsur taluk of Mysuru district and Koraga tribe from Sulya taluk of Dakshina Kannada district. Descriptive research design was adopted for the study.  Primary data was collected through a structured interview schedule and focus group discussion. The sample size Judgemental sampling and convenience sampling technique was used to select the sample. The sample size consists of 200 respondents from Jenukuruba tribe and 50 respondents from Koraga tribe. The study reveals that majority of the respondents were illiterates and they belong to middle aged group. Most of them belonged to low-income group and their social participation was very poor.